STRATEGI KOMUNIKASI BENCANA OLEH BADAN PENANGGULANGAN BENCANA PADA KEGIATAN DESA TANGGUH BENCANA (DESTANA) - Hariati Br Ginting; Prietsaweny RT Simamora (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
Indonesia as a country located in the ring of fire circum has caused many volcanoes in Indonesia. Most of the people also live in areas close to volcanoes this makes disasters like eruptions unavoidable. Communication is required in all aspects of life, including in the context of disasters. One of the disaster management agencies or Institutions is the Regional Disaster Management Agency (BPBD). This study aims at finding how the Disaster Communication Strategy by BPBD Karo Regency in Disaster Resilient Village Activities. Data collection techniques used are in-depth interviews, observations, and literature studies. The data used in this study are primary data collected from the field. Research methods is qualitative approach. There were 6 informants in this study. Based on the research results, the conclusion is that the strategy in selecting communicators is seen from the point of view of credibility, attractiveness, and strength of the communicators, namely the sources. The credibility of the sources possessed is the extensive knowledge related to disasters, attitudes and personalities that are favored by the community, as well as sufficient experience to become a communicator. the attraction that has able to attract people to come to listen to the material. In the Strategy of Reviewing the Message Conducted by the Regional Disaster Management Agency (BPBD) it is education and selection of communication media used by the Regional Disaster Management Agency (BPBD), namely old media in the form of old media, outdoor media in the form of banners, billboards, and Umbul-Umbul, and media new in the form of social media Facebook and the WA Group.